Hangman's curse [videorecording (DVD)] - Zielinski, Rafal; Keith, David, 1954-; Harris, Mel, 1957-; Meester, Leighton, 1986-; Smith, Douglas, 1985-; Moses, William R.; Peretti, Frank E. (Witness Entertainment, Inc. : Distributed by 20th Century Fox Home Entertainment, 2004)
Within the shadowed corridors of Rogers High School, the students are claimed by a deadly power. Nate and Sarah and their two teenage children race to protect the students from the mysterious forces around them ... and from their own prejudices.